2009 IEEE International Workshop on Antenna Technology 2009
DOI: 10.1109/iwat.2009.4906966
|View full text |Cite
|
Sign up to set email alerts
|

Electric field distributions around the human body with a small antenna in the frequency range of 2.5 MHz to 2.5 GHz

Abstract: In recent years, body-centric wireless communications become an active area of research due to their various applications such as e-healthcare, support systems for specialized occupations, and personal communications. Since the candidate frequencies for body-centric wireless communications widely range from MHz to GHz, dielectric properties of the human body tissues, relative dimensions of the human body to wavelength, and the propagation channels around the body extremely vary with frequencies. In this paper,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Lastly the levels at the ears are relatively stable; however, one deep null is found at 300 MHz when the model is raising the hand. Incidentally, we have already confirmed that the presence of the earth ground has little effect on the channels [6].…”
Section: B Received Open Voltage With Different Posturessupporting
confidence: 66%
See 2 more Smart Citations
“…Lastly the levels at the ears are relatively stable; however, one deep null is found at 300 MHz when the model is raising the hand. Incidentally, we have already confirmed that the presence of the earth ground has little effect on the channels [6].…”
Section: B Received Open Voltage With Different Posturessupporting
confidence: 66%
“…In recent years, body-centric wireless communications have become an active area of research due to their various applications such as e-healthcare, support systems for specialized occupations, and personal communications [1]- [6]. Whereas UHF bands are subjects of interest especially in Europe, relatively low frequency bands below several megahertz are also in researchers' and corporations' interest especially in Japan [4], [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further information on 3D character animation using motion capture can be found in [17]. C. Avatar Tissue Material Following the work of [6], [7], [18], an homogeneous tissue value of 2/3 that of muscle ( r = 35 and = 1.16 S/m) was used for the avatar and validated by S 21 measurement at 2.45 GHz. The simulation used the parameters in Table I where the inclusion of a concrete floor was found to be necessary when antennas were mounted below the waist.…”
Section: Human Avatars Creationmentioning
confidence: 99%